#recovery – creating common ground through visual and textual information shared in the eating disorder recovery community on Instagram - Bressel, Paulina (Information Research an international electronic journal, 2025)
Introduction. This exploratory study contributes to information practice research, aiming at increasing the understanding of the perspective of individuals in the social setting of a health community by focusing on the common ground created through shared information. The investigation concentrates on individuals sharing health information in an eating disorder recovery community on Instagram. Method. This study analyses representations of eating disorder recovery on Instagram, focusing on visual and textual shared information. The Instagram posts (pictures and texts) were collected structurally with a crawler based on four selected hashtags. Analysis. The analysis was data-driven, using qualitative and quantified content analysis. The centre of analysis was on image types, and structure, tone and content of the captions. Results. Four types of posts emerged that represent the common ground of affected individuals on Instagram: the Eating Disorder Recovery diary, the proof of eating, the personal transformation, and affirmations. Reflections on community participation and the information practice of sharing were identified. Conclusion. This study provides a deeper understanding of the eating disorder recovery community on Instagram, offering insights into the individuals' personal experiences and thoughts on eating disorder recovery, as well as topics essential for individuals going through recovery. Further, first insights on the health information sharing practices of individuals in eating disorder recovery were gained.